Could Nanotechnology Help to End the Fight Against COVID-19? Review of Current Findings, Challenges and Future Perspectives - Yayehrad AT (Dove Medical Press, 2021)
Ashagrachew Tewabe Yayehrad,1,2 Ebrahim Abdela Siraj,1,2 Gebremariam Birhanu Wondie,1 Atlaw Abate Alemie,1,3 Manaye Tamrie Derseh,1,4 Abyou Seyfu Ambaye4 1Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pharmacy, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 3Ethiopian Food and Drug Authority (EFDA), Federal Ministry of Health (FMoH), Addis Ababa, Ethiopia; 4Departement of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Ashagrachew Tewabe YayehradDepartment of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, PO Box: 9086, Addis Ababa, EthiopiaTel + 251912960525Email ashutewabe@gmail.comAbstract: A serious viral infectious disease was introduced to the globe by the end of 2019 that was seen primarily from China, but spread worldwide in a few months to be a pandemic. Since then, accurate prevention, early detection, and effective treatment strategies are not yet outlined. There is no approved drug to counter its worldwide transmission. However, integration of nanostructured delivery systems with the current management strategies has promised a pronounced opportunity to tackle the pandemic. This review addressed the various promising nanotechnology-based approaches for the diagnosis, prevention, and treatment of the pandemic. The pharmaceutical, pharmacoeconomic, and regulatory aspects of these systems with currently achieved or predicted beneficial outcomes, challenges, and future perspectives are also highlighted.Keywords: nano-vaccine, nano-theranostics, nanoparticles, nanotechnology, SARS-CoV-2